Analisis Implementasi Kurikulum Merdeka di SMA Negeri 1 Sei Rampah - Hia, Susi Susanti; Siahaan, Mian; Pardede, Sanggam (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to describe: 1) to analyze the implementation of the independent curriculum in learning at SMA Negeri 1 Sei Rampah, 2) to analyze the obstacles and constraints in implementing the independent curriculum in learning at SMA Negeri 1 Sei Rampah, 3) to analyze efforts to overcome obstacles and Obstacles in implementing the independent curriculum in learning at SMA Negeri 1 Sei Rampah. This research is a qualitative research. The research was carried out at SMA Negeri 1 Sei Rampah in April 2024. The subjects of this research were the Principal, Class X Teachers, and Class X Students. Data collection techniques were carried out using observation, interviews, and documentation. Activities in qualitative data analysis using interactive models are data collection, data reduction, display, and conclusion drawing. The results of this research show that: 1) the implementation of the independent curriculum in learning has been well realized, and the planning carried out was by analyzing CP, compiling TP, and creating ATP. The implementation of the learning has implemented differentiated learning adapted to student needs and has prepared evaluations in the form of diagnostic assessments, and formative and summative assessments, 2) there are constraints and obstacles such as less valid information, few reference sources, limited time in preparing teaching and assessment modules, 3) efforts made to overcome constraints and obstacles, namely by conducting teacher training and coaching, increasing resources and facilities, student guidance and development programs, and collaboration and financial assistance